Deep Ecological Consciousness and Interconnectedness in William Wordsworth’s Tintern Abbey - Bhandari, Rupsingh (Technium Social Sciences Journal, 2022)
Humans and nature interconnectedness is a dynamic process. The extensive misuse of natural resources has left us in an uncontrolled situation. Ecological disasters are worsening our relationship with nature. Humans’ anthropocentric attitude to dominate nature needed to be relooked from biocentric lenses. Rediscovering our interconnectedness with nature will advance our ecological consciousness to bring equilibrium between humans and nature. This paper intends to examine “Tintern Abbey”, the famous poetry by William Wordsworth to raise awareness of the interconnectedness of humans and nature in people’s minds, through deep ecological perspectives.